Domain boundaries in silicene: Density functional theory calculations on electronic properties*Project supported by the National Natural Science Foundation of China (Grant Nos. 61390501 and 51325204), the National Basic Research Program of China (Grant Nos. 2011CB808401 and 2011CB921702), and the Tainjin Supercomputing Center, Chinese Academy of Sciences. (August 2015) - Xiao, Hong-Jun; Zhang, Li-Zhi; Du, Shi-Xuan; Gao, Hong-Jun
Abstract By using density functional theory (DFT)-based first-principles calculations, the structural stability and electronic properties for two kinds of silicene domain boundaries, forming along armchair edge and zigzag edge, have been investigated. The results indicate that a linkage of tetragonal and octagonal rings (4|8) appears along the armchair edge, while a linkage of paired pentagonal and octagonal rings (5|5|8) appears along the zigzag edge. Different from graphene, the buckling properties of silicene lead to two mirror symmetrical edges of silicene line-defect. The formation energies indicate that the 5|5|8 domain boundary is more stable than the 4|8 domain boundary. Similar to graphene, the calculated electronic properties show that the 5|5|8 domain boundaries exhibit metallic properties and the 4|8 domain boundaries are half-metal. Both domain boundaries create the perfect one-dimensional (1D) metallic wires. Due to the metallic properties, these two kinds of nanowires can be used to build the silicene-based devices.